2021
DOI: 10.1038/s41388-021-01848-9
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear scaffold protein p54nrb/NONO facilitates the hypoxia-enhanced progression of hepatocellular carcinoma

Abstract: Hypoxia and related oxidative stress are closely related to the development and treatment of hepatocellular carcinoma (HCC). However, the mechanism mediated by hypoxia in HCC has not yet been elucidated. Here, we found multifunction scaffold protein p54nrb/NONO exerted pleiotropic effects to regulate hypoxia transcription signals, thereby enhancing the progression of liver cancer. Extensive analysis of clinical data demonstrated that NONO was significantly upregulated and represented as a poor prognostic indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…52 In addition, NONO is involved ERK1/2, PI3K/AKT signaling pathways in cancer cells. 53,54 In the present study, we found that NONO deficiency impaired BCR-induced multiple signaling pathways in primary B cells, which include PI3K-AKT, ERK1/2 and NF-κB pathways. The mechanism on how NONO regulates BCR signaling is unclear.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…52 In addition, NONO is involved ERK1/2, PI3K/AKT signaling pathways in cancer cells. 53,54 In the present study, we found that NONO deficiency impaired BCR-induced multiple signaling pathways in primary B cells, which include PI3K-AKT, ERK1/2 and NF-κB pathways. The mechanism on how NONO regulates BCR signaling is unclear.…”
Section: Discussionsupporting
confidence: 52%
“…For instance, NONO directly interacts with ERK1/2 and thus regulates PDGF‐induced ERK1/2 activation in vascular smooth muscle cells 35 ; NONO interacts with NF‐κB and thus enhances NF‐κB nuclear translocation and phosphorylation 52 . In addition, NONO is involved ERK1/2, PI3K/AKT signaling pathways in cancer cells 53,54 . In the present study, we found that NONO deficiency impaired BCR‐induced multiple signaling pathways in primary B cells, which include PI3K‐AKT, ERK1/2 and NF‐κB pathways.…”
Section: Discussionsupporting
confidence: 51%
“…Considering that the heart has a voracious requirement for energy 34 . Besides, Numerous studies have shown that NONO regulates energy metabolism in cancer cells 35 , 36 . We detected the total cellular ATP content, mitochondrial and glycolysis stress tests utilizing the Seahorse XF technology.…”
Section: Discussionmentioning
confidence: 99%
“…33 NONO interacts with the hypoxia inducible factor-1/2 complex and its downstream transcripts to activate the transcription of hypoxia-induced genes, which facilitate HCC progression. 34 CENPI, a member of the centromere protein family, has an essential role in accurate chromosome segregation. 35 CENPI is upregulated in multiple cancers and serves as an oncogene to promote tumor cell proliferation, migration and invasion.…”
Section: Dovepressmentioning
confidence: 99%